Parental reports of communicative development at the age of 36 months: The Estonian CDI-III. Issue 1 (February 2020) - Tulviste, Tiia; Schults, Astra
Parental reports are a widely-used source of information about infants' and toddlers' communicative skills, but parent-report instruments valid for children older than 30 months are less known. This study explored individual variability in children's communicative skills at the age of 3;0 via parental reports using the Estonian (E) CDI-III. The validity of ECDI-III was established through correlations with another parent-report instrument (ECDI-II) and a standardized examiner-administered language assessment (New Reynell Developmental Language Scales; NRDLS). A hundred Estonian-speaking children ( M age = 35.77 months, age range from 34 to 39 months; 20 of them with reported language difficulties) participated in the study. Relations between different communicative skills and the impact of such factors as the child's gender, maternal and paternal education, reported language difficulties, the number of siblings, and day care attendance on variability in vocabulary size were also considered. The results showed that the ECDI-III components were moderately to strongly associated with each other, with the ECDI-II and NRDLS. Children with reported language difficulties scored lower on all language measures, except for orthographic awareness. Girls, children of more educated mothers, children with older siblings, and those who had attended day care for more months obtained higher vocabulary scores.